Hematological indices and iron status in athletes of various sports and performances - Schumacher, Y. O.; Schmid, A.; Grathwohl, D.; Bultermann, D.; Berg, A. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: Alterations of the red blood cell system and iron metabolism can influence physical performance. On the other hand, exercise can influence hematological variables. The purpose of this epidemiological study was to investigate the characteristics of the red blood cell system and the iron metabolism in athletes of different sporting disciplines and at different levels of performance. METHODS: We studied 851 male subjects (747 athletes, 104 untrained controls). Hemoglobin (Hb), hematocrit (Hct), red blood cell count (RBC), iron, transferrin, ferritin (Fer), and haptoglobin were analyzed in standardized blood samples, obtained after 2 d of rest, considering levels of performance (internationally, nationally, locally competitive, and leisure time), distinctive sporting category (endurance- (END), strength- (POW), and mixed-trained (MIX)), and, within endurance athletes, distinctive disciplines (cycling (CYC) and running (RUN)). RESULTS: No difference was found between athletes and controls in Hb and Hct. Reduced Hb, Hct, and RBC levels were observed in END compared with POW and MIX. These findings can mainly be attributed to exercise-induced plasma volume expansion, and only to a lesser degree and in selected athlete populations to hemolysis, as low haptoglobin is only observed in RUN, not in CYC, suggesting that not exercise itself but the "traumatic" movement of running might trigger the destruction of red blood cells. Physical activity of increasing duration and workloads (leisure time compared with competitive athletes) leads to decreased Fer levels in athletes, disregarding their discipline, but more pronounced in RUN. CONCLUSION: Physical training itself has no significant effect on selected hematological variables in athletes compared with untrained controls. The specific type and duration of exercise is of major importance in the adaptations of the blood cell system and the iron metabolism.